2014
DOI: 10.1002/anie.201407365
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Fabrication of Pseudocapacitive Glass Windows that Combine Electrochromism and Energy Storage

Abstract: Multifunctional glass windows that combine energy storage and electrochromism have been obtained by facile thermal evaporation and electrodeposition methods. For example, WO3 films that had been deposited on fluorine-doped tin oxide (FTO) glass exhibited a high specific capacitance of 639.8 F g(-1). Their color changed from transparent to deep blue with an abrupt decrease in optical transmittance from 91.3% to 15.1% at a wavelength of 633 nm when a voltage of -0.6 V (vs. Ag/AgCl) was applied, demonstrating its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
141
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 215 publications
(147 citation statements)
references
References 31 publications
6
141
0
Order By: Relevance
“…Very recently, WO 3 has been demonstrated very interesting and promising bifunctionalities that combine electrochromism and pseudocapacitance. 29,30 Deeper understanding of the pseudocapacitance of WO 3 is needed to develop what we refer to as "electrochromic supercapacitors" with better performance.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, WO 3 has been demonstrated very interesting and promising bifunctionalities that combine electrochromism and pseudocapacitance. 29,30 Deeper understanding of the pseudocapacitance of WO 3 is needed to develop what we refer to as "electrochromic supercapacitors" with better performance.…”
Section: Introductionmentioning
confidence: 99%
“…4a) reveals the existence of elements C, O, W and Cu, where the Cu signal originates from the TEM copper grid. 27 The electrochemical properties of the as-prepared CNT and CNT-WO 3 electrodes were studied using a three-electrode conguration with an Ag/AgCl electrode as the reference electrode, a graphite rod as the counter electrode, and 1 M H 2 SO 4 aqueous solution as the electrolyte. 4b.…”
Section: Resultsmentioning
confidence: 99%
“…25 Liang et al revealed ultrathin WO 3 nanosheets and used them to fabricate exible electrochromic devices. 27 The problem of the relatively low energy density of the assembled SC device is critical. 27 The problem of the relatively low energy density of the assembled SC device is critical.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Yang et al designed multifunctional glass windows that combine energy storage and electrochromism using WO 3 film electrodes which were obtained by facile thermal evaporation method (Fig. 5a-c) [50]. These WO 3 films exhibited a high specific capacitance of 639.8 F g À1 .…”
Section: Materials Candidates Metal Oxidesmentioning
confidence: 99%